Long‐Term Safety of Extremely Low‐Dose Amiodarone at 50 mg Daily in Patients With Persistent Atrial Fibrillation - Kentaro Yoshida; Yuta Okabe; Masako Baba; Ko Funabashi; Mami Narita; Shunsuke Kuchitsu; Akinori Sugano; Hideyuki Hasebe; Tomoko Ishizu; Noriyuki Takeyasu (Journal of Arrhythmia)
ABSTRACT Background Rhythm control of atrial fibrillation (AF) by pulmonary vein isolation alone is commonly difficult in this aging society, and the role of pharmacological therapy is being revisited. Identifying the lowest dose of amiodarone is important as this drug causes dose‐ and duration‐related lung toxicity. Long‐term safety of the use of extremely low‐dose amiodarone in Japanese patients was retrospectively evaluated. Methods Included were 120 patients treated with extremely low‐dose amiodarone (50 mg daily) for persistent AF. KL‐6 level was systematically measured at baseline and every 3 months thereafter. The patients were classified into a different quartiles (Q) based on the KL‐6 level measured at baseline (Q1, Q2, Q3, and Q4). Thyroid function was also evaluated at each follow‐up. Results During a mean follow‐up period of 51 months, KL‐6 elevation (> 700 U/mL) occurred in 7 (5.8%) patients with higher baseline KL‐6 (Q1, 0 patients; Q2, 0 patients; Q3, 1 patient; and Q4, 6 patients; p = 0.0018). Interstitial pneumonia (IP) was diagnosed in 1 (0.8%) patient in Q3 who recovered without the use of steroids. ROC curve analysis showed a cut‐off value for KL‐6 of 283 U/mL for predicting the subsequent elevation. Approximately 70% of the patients were free from recurrence of AF, although electrical cardioversion was required to restore sinus rhythm in 58 (48%) of them. Conclusions Even an extremely low dose of amiodarone may potentially contribute to maintenance of sinus rhythm in highly selected patients with persistent AF. A low baseline KL‐6 level may indicate patients at lower risk for amiodarone‐related IP.